2021
DOI: 10.1186/s13287-021-02548-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum-free medium and hypoxic preconditioning synergistically enhance the therapeutic effects of mesenchymal stem cells on experimental renal fibrosis

Abstract: Background Mesenchymal stem cells (MSCs) repair injured tissue in a paracrine manner. To enhance their therapeutic properties, preconditioning with various factors has been researched. We have previously showed that MSCs cultured in serum-free medium (SF-MSCs) promote their immunosuppressive ability, thereby enhancing their anti-fibrotic effect. Here, we examined whether serum-free medium and hypoxic preconditioning synergistically enhance the therapeutic effects of MSCs on renal fibrosis in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Furthermore, stem cells (e.g., BMSCs) are capable of secreting a variety of cytokines, such as HGF and TGFβ1, to regulate various biological processes in organisms; however, highly sensitive visualization of the complex intercellular signal transductions and intracellular signaling pathways in this process is a big challenge. The dimerizations of cell membrane proteins induced by the stem cell secretions were imaged by SERS to reveal the key role of stem cells in bioregulation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, stem cells (e.g., BMSCs) are capable of secreting a variety of cytokines, such as HGF and TGFβ1, to regulate various biological processes in organisms; however, highly sensitive visualization of the complex intercellular signal transductions and intracellular signaling pathways in this process is a big challenge. The dimerizations of cell membrane proteins induced by the stem cell secretions were imaged by SERS to reveal the key role of stem cells in bioregulation.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of inflammatory licensing pervades the field of MSC biology. Previous studies by our group and others have evaluated the effects of inflammatory cytokines ( 4 , 12 , 14 16 , 21 , 24 , 39 , 51 ), hypoxia ( 23 , 24 ), serum starvation ( 25 , 26 ), and numerous other culture manipulations. Mechanotransduction of MSC is particularly interesting for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Not wholly anti-inflammatory, the MSC response elicited by these cytokines can include classical pro-inflammatory signals, such as chemokines, metalloproteins, and TNF-α ( 4 , 10 , 12 , 13 , 22 ). Other priming studies have employed culture manipulations to pre-activate MSC including the use of hypoxia ( 23 , 24 ) and low serum ( 25 , 26 ). While promising, these approaches carry additional associated costs as well as down-stream complications to large-scale cell manufacturing regulatory approval ( 5 , 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ishiuchi's study found that serum-free culture and hypoxic pretreatment synergistically enhanced the therapeutic effects of MSCs on renal fibrosis and that hypoxia transformed cellular metabolism into glycolysis. Therefore, it is speculated that the production of antiinflammatory MSCs can be induced by regulating the metabolic reprogramming of MSCs (26).…”
Section: Application Of Anti-inflammatory Msc In the Treatment Of Imm...mentioning
confidence: 99%